Lindernia procumbens in Poland: the relationship between weather conditions and the occurrence of the species - Nobis, Agnieszka; Nobis, Marcin; Piotrowicz, Katarzyna; Kącki, Zygmunt; Dajdok, Zygmunt (Biodiversity: Research and Conservation, 2011)
New data regarding the occurrence of Lindernia procumbens (prostrate false pimpernel) are discussed and its current geographical range in Poland is given. A comparison of its past and present distribution in Poland indicates an advancement of the distribution limit northwards, which may be caused by climate changes, mostly, by an increased number of heat waves in the warm half-year. The relationship between the occurrence of the species and specific meteorological conditions, especially, unusually hot and dry summer periods, is analysed using long-term meteorological surveys.